Using polyacrilamide with sprinkler irrigation to improve infiltration - Bjorneberg, David (2003)
ABSTRACT: Center-pivot irrigation systems often apply water at rates greater than the soil infiltration rate. Applying high molecular weight, water-soluble, anionic polyacrylamide (PAM) to the soil can improve infiltration and reduce soil erosion The objective of this study was to determine whether single and multiple PAM applications with sprinkler irrigation improved infiltration under field conditions. A two-year study conducted near Kimberly, Idaho, used a solid-set sprinkler system, and a one-year study conducted in Monte dos Alhos near Alvalade do Sado, Portugal, used a center pivot. At Kimberly, applying PAM with four irrigations (total applied PAM was 2.1 kg ha−1 in 2000 and 3.0 kg ha−1 in 2001) significantly reduced total measured runoff, from 5.9 mm (2000) and 9.2 mm (2001) for the control to 2.0 and 2.1 mm. Total measured soil erosion was also reduced from 52 and 34 kg ha−1 for the control to 21 and 5 kg ha−1 for the multiple PAM treatment. Applying similar or greater amounts of PAM with a single irrigation reduced erosion, but not runoff, compared with the control. In the Monte dos Alhos study, runoff was reduced by applying a total of 0.3 kg PAM ha−1 with a single irrigation (43 mm runoff) or three irrigations (65 mm runoff) compared with the control (111 mm runoff). Measured soil erosion was not significantly different among treatments. Applying PAM with multiple irrigations extended its effectiveness as long as the application rate was great enough to adequately stabilize the soil surface during the first irrigation.